FFC NMR relaxometer with magnetic flux density control - Roque, Antonio (2019)
This paper describes an innovative solution for the power supply of a fast field cycling (FFC) nuclear magnetic resonance (NMR) spectrometer considering its low power consumption, portability and low cost. In FFC cores, the magnetic flux density must be controlled in order to perform magnetic flux density cycles with short transients, while maintaining the magnetic flux density levels with high accuracy and homogeneity. Typical solutions in the FFC NMR literature use current control to get the required magnetic flux density cycles, which correspond to an indirect magnetic flux density control. The main feature of this new relaxometer is the direct control of the magnetic flux density instead of the magnet current, in contrast with other equipment available in the market. This feature is a great progress because it improves the performance. With this solution it is possible to compensate magnetic field disturbances and parasitic magnetic fields guaranteeing, among other possibilities, a field control below the earth magnetic field. Experimental results validating the developed solution and illustrating the real operation of this type of equipment are shown.